Perspective of the comparative effectiveness of non-pharmacologic managements on postpartum hemorrhage using a network meta-analysis - Kyung Ju Lee; Kwan Hong; Hari Hwang; Hijeong Choi; Sangho Sohn (Korean Society of Obstetrics and Gynecology, 2020)
Objective Postpartum hemorrhage (PPH) is the leading cause of maternal mortality worldwide and is both unpredictable and inevitable. While uterotonic drugs are routinely recommended, there is ongoing debate on the ideal intervention to control uterine bleeding. This review aims to compare the use of non-pharmacologic treatments with peripartum hysterectomy in cases of life-threatening uncontrolled obstetric hemorrhage. The review's objective is to use a network meta-analysis to help prevent maternal deaths and rank the treatments according to success rates. Methods We searched MEDLINE (PubMed), Embase, and the Cochrane Library, from January 2014 until December 2018. A second search was carried out in April 2019 before the final data analysis. Network meta-analysis allows for the calculation of the effect size between treatment groups through indirect treatment comparison. Results We confirmed that balloon-assisted management is the best intervention for uncontrolled postpartum bleeding with pharmacologic treatment. This is followed by uterine artery embolization and surgical procedures, which can help avoid the need for a hysterectomy. The balloon tamponade demonstrated lower failure rate than the surgical procedure with odds ratio (OR) of 0.44 and 95% confidence intervals (CIs) 0.50-30.54. Uterine artery embolization had a lower risk for hysterectomy than the surgical procedure group (OR, 0.74; 95% CI, 0.22-2.50). Conclusion For the quick treatment of postpartum bleeding, balloon tamponade is the best method for uncontrolled postpartum bleeding with pharmacologic treatment, followed by uterine artery embolization and surgical procedures.